Triglyceride-glucose index as a predictor of the risk of sarcopenia in elderly patients with OSA: a multicenter study - Libo Zhao; Xueqin Shen; Yinghui Gao; Weimeng Cai; Dong Rui; Xin Xue; Zhe Zhao; Xiaoshun Qian; Junling Lin; Li Fan; Lin Liu (Diabetology & Metabolic Syndrome)
Abstract Background Given the clear association between obstructive sleep apnea (OSA) and metabolic disorders, coupled with a limited understanding of sarcopenia in patients with OSA, this study aimed to investigate the relationship between triglyceride-glucose (TyG) index and sarcopenia and in an elderly population with OSA. Methods Multiple hematological and sleep-breathing status were meticulously recorded in the cohorts. The SARC-F scale ≥ 4 was considered indicative of probable sarcopenia. The correlations between clinical indicators and the SARC-F score were analyzed. The area under the curve (AUC) was utilized to assess the predictive ability of TyG for sarcopenia and sarcopenic obesity. Logistic regression analysis and sensitivity stratification were employed to explore the influence of TyG. Results A total of 1,148 individuals were included, among whom the median age was 66 (62, 71). 46.3% (n = 531) were diagnosed with severe OSA, while 24.0% (n = 276) had probable sarcopenia. The SARC-F score exhibited positive correlations with TyG (r = 0.122, P < 0.01), but it was negatively correlated with mean peripheral oxygen saturation (mean SpO2, r = -0.157, P < 0.01). The AUC for assessing sarcopenia using TyG was 65.7% (95% confidence intervals (95%CI): 61.9–69.5%. Furthermore, the cutoff value for TyG was 8.855 (sensitivity = 67.4%, specificity = 62.8%). Logistic regression and stratified sensitivity analyses, adjusted for various influencing factors, collectively revealed that TyG was a risk-related predictor of probable sarcopenia (all odds ratio > 2.0, P < 0.05). Conclusions The TyG index emerges as an independent predictor of sarcopenia in patients with OSA, shedding light on the complex interplay between nighttime hypoxia and muscle health.